Determining of Cross Sections for 16O(n,Î±)13C reaction from Cross Sections of 13C(Î±,n)16O for the ground state - Ebrahiem, Sameera A.; Sarsam, Maher N.; Youhana, Hermez M.; Abd-Al-Hameed, Nebras T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, light elements for 13C , 16O for (Î±,n) and (n,Î±) reactions as well as Î±-particle energy from 2.7 MeV to 3.08 MeV are used as far as the data of reaction cross sections are available. The more recent cross sections data of (Î±,n) and (n,Î±) reactions are reproduced in fine steps 0.02 MeV for 16O (n,Î±) 13C in the specified energy range, as well as cross section (Î±,n) values were derived from the published data of (n,Î±) as a function of Î±-energy in the same fine energy steps by using the principle inverse reactions. This calculation involves only the ground state of 13C , 16O in the reactions 13C (Î±,n) 16O and 16O (n,Î±) 13C.